TI_GERICHTE 16.2017.28 vom 29. April 2019 , Contratto di assicurazione: sinistro - frodi nelle giustificazioni - TI Tribunale d'appello (2019)
Contratto di assicurazione: sinistro - frodi nelle giustificazioni